Online Learning Difficulties Analysis for Class of 2020 Students Universitas Negeri Medan for Lower Organism Taxonomy Course - Elvida Harianti Harahap (Jurnal Pelita Pendidikan, 2023)
The purpose in this research was to find out the learning difficulties of Biology students Universitas Negeri Medan during online learning and factors that cause learning difficulties. The research method uses a descriptive qualitative approach. The research population is Biology students Universitas Negeri Medan, the sample used is PSBD D and PSBD E 2020 students. The instrument used is a questionnaire distributed using a google form. The results of the research based on the DPNA score, the level of learning difficulty experienced by Biology students Universitas Negeri Medan is relatively low. Even though student scores were in the good category, it turned out that PSBD D and PSBD E students in 2020 experienced several difficulties during online learning, including: difficulty understanding the topic in Lower Organism Taxonomy course with an average of 68%. Did not understand the explanation given by the lecturer with an average of 47%. Did not understand the instructions given by the lecturer during the learning process with an average of 57%. Difficulty understanding the features contained in the SIPDA system with an average of 26%. Experienced difficulties in accessing the internet network during the online learning process with an average of 60%. Experienced quota limitations during the online learning process with an average of 43%. The factors causing learning difficulties for biology students class of PSBD D and PSBD E 2020 include internal factors and external factors. Based on internal factors with an average of 58% classified as difficult enough. While external factors with an average of 59% are classified as difficult enough.